Pembelajaran Tematik Madrasah Ibtidaiyah Berbasis Portofolio - Marzuki, Susilawati; J Sarafuddin, Nandini; Paleha, Istiqoma; Nurjannah, Nurjannah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This journal was written to find out how Portfolio-Based SD / MI Thematic Learning is. The method in this article uses library research, which is a method of collecting data by understanding and studying theories from various literature related to this research. The success achieved by students at the Madrasah Ibtidaiyah / Elementary School level is one of the main determinants at the next level. Portfolio-based thematic learning is learning based on understanding which illustrates that students form or build their own knowledge through interaction with their environment which has an impact on knowledge construction, understanding, and experience carried out individually or in groups where students are required to think intelligently, creatively, participatively and responsibly. From the several journals studied, it was explained that these journals had carried out the steps of the portfolio-based learning model well.